Peningkatan Pembelajaran Materi Cerita Fiksi di Sekolah Dasar melalui Model Numbered Heads Together Dengan Media Audio - Kurniawan, Oky (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The learning outcomes of fiction story material for 4th graders of Mandala 02 State Elementary School (SDN) Cimanggu District, Cilacap Regency were still low. The researcher applied the numbered heads together (NHT) learning model with audio as a media. This study used a Classroom Action Research (CAR) that designed in two cycles. The results showed that their average value of the class during the pre-test was 52.65, increased in the post-test results to 79.28 with an increase in classical learning completeness from 21.88% to 88.57%. Student learning activities in the first cycle of 73.91% increased in the second cycle to 77.76%. The teacher's performance score had reached the indicator of success with the final score in the first cycle of 82.5 increasing in the second cycle to 84.25. The application of the NHT learning model with audio media could improve Indonesian learning of fiction story material.